Percepatan Pertumbuhan Usaha Mikro, Kecil dan Menengah (UMKM) Melalui Perkuatan Lembaga Keuangan Mikro Syariah (LKMS) di Jawa Timur - Renny Oktafia (Proceedings of Annual Conference for Muslim Scholars, 2017)
Economic growth rate in East Java is higher, when compared with the national economic growth rate. In this case, one of them because of being supported by the existence of Micro, Small and Medium Enterprises (MSMEs) in East Java. With the continuing running of SMEs in East Java, it will be able to absorb more labor, and ultimately lower unemployment rate in East Java. To continue to support the economy in East Java, MSMEs need to be supported in order to survive and continue to grow. One form of support for the sustainability of SMEs, namely through easy access capital for MSMEs. Capital support for MSMEs, can be obtained through Sharia Micro Finance Institution (LKMS) through partnership program. To be able to provide maximum capital services for MSMEs, then LKMS must be strengthened institutionally. The strength of LKMS institutionally can be realized by implementing linkage program between LKMS and sharia bank.